Convergent Validity of Three Measures of Reflective Function: Parent Development Interview, Parental Reflective Function Questionnaire, and Reflective Function Questionnaire - Lubna Anis (Frontiers in Psychology, 2020)
Reflective function (RF) is defined as an individual’s ability to understand human behavior in terms of underlying mental states including thoughts, feelings, desires, beliefs, and intentions. More specifically, the capacity of parents to keep their child’s mental states in mind is referred to as parental RF. RF has been linked to adult mental health and parental RF to children’s mental health and development. The gold standard measure of RF is the interview-based Reflective Functioning Scale (RFS) applied to the Parent Development Interview (PDI) or Adult Attachment Interview (AAI), which while well validated, is time-and labor-intensive to administer. Given the increasing need for reliable, valid, and rapid RF assessment in wide-ranging settings, two alternative measures were considered including the Reflective Function Questionnaire (RFQ) and Parental Reflective Function Questionnaire (PRFQ). We determined the convergent validity of these measures in comparison with the PDI-rated RFS. A sample of mothers and fathers (n = 150) was drawn from a sub-study of the ongoing Alberta Pregnancy Outcomes and Nutrition (APrON) longitudinal cohort when their children were 42–60 months of age. Pearson correlations and multiple linear regression was conducted, followed by splitting the sample to compute Cohen’s kappas measures of agreement. Two subscales of the PRFQ correlated significantly (p < 0.05) with the gold standard PDI-rated RFS, providing evidence for convergent validity. As a brief multidimensional measure of parental RF, the PRFQ offers an alternative for measurement of RF in large-scale studies of parental development and child health.